Structural changes of the vascular wall in patients with chronic cerebral ischemia depending on the presence of the metabolic syndrome and the concentration of the vasculoendothelial growth factor - I. V. Darii (Kazimierz Wielki University, 2019)
Background. Chronic inflammation and enhancement of free-radical oxidation follow metabolic syndrome. Nowadays, much attention is paid to vasculoendothelial growth factor, one of the most important factors of endothelial dysfunction. There is an evidence of its possible involvement in degenerative and atherosclerotic vascular processes. The objective: to determine changes in the structure of the vascular wall in patients with chronic cerebral ischemia, depending on the presence of metabolic syndrome and the concentration of vasculoendothelial growth factor. Materials and methods. In a prospective study 49 patients with chronic cerebral ischemia were examined. The patients were randomized into 2 groups: the main group consisted of 27 patients with chronic cerebral ischemia with metabolic syndrome. There were 22 patients with chronic cerebral ischemia without metabolic syndrome in the comparison group. The severity of atherosclerotic lesions of the arteries of the head and neck was investigated taking into account the structural changes of the vascular wall, the presence of intraluminal formations, as well as their ultrasonic characteristics. In the serum of the studied patients the concentration of vasculoendothelial growth factor was measured by enzyme-linked immunosorbent assay. Results. At the concentration of vasculoendothelial growth factor >300 pg/l, differentiation into layers of the intima-media complex was more often lost in patients of the main group than in patients of the comparison group: 35.7% and 0% of the examined, respectively. At this biomarker concentration, excess thickness of the intima-media complex of the common carotids (≥0.9 mm) was observed in 36.4% of patients in the main group versus 13.4% in patients in the comparison group. Also at a concentration of vasculoendothelial growth factor >300 pg/l in patients of the main group the presence of plaques was observed in 33.3%, while in patients in the comparison group plaques were not observed. Conclusions. Early and late manifestations of atherosclerotic structural vascular lesions in chronic cerebral ischemia with metabolic syndrome may have another quantitative biomarker of vascular endothelial damage. In these patients, the manifestations of the atherosclerotic process at all stages occur at a concentration of vasculoendothelial growth factor >300 pg/l, while atherosclerotic changes in patients without metabolic syndrome are minimal at this concentration.